2021
DOI: 10.1007/s12144-021-02098-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Turkish version of the behavior assessment for children (BAC) scale

Abstract: Behavioral problems are seen in one out of four school-age children. There are difficulties in evaluating children's behavior in Turkish culture and therefore a valid and reliable measuring tool is needed for assessing behavioral problems in this age group. The aim of this study was to evaluate the psychometric properties of the Turkish version of the Behavior Assessment for Children (BAC). The study was conducted using the cross-sectional data collection method to examine the content validity, factor structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Split-half method refers to splitting a body of supposedly homogeneous data into two halves and calculating the results separately for each to assess their reliability by using Spearman-Brown formula and Guttmann split-half formula (27). Reaching a value of .70 and above represents a reliable measurement for the scale (26). In our study, Spearman Brown split-half correlation was found 0,702 and Guttman Split-half coefficient was calculated as .70 (Table 3).…”
Section: Reliabilitymentioning
confidence: 55%
See 2 more Smart Citations
“…Split-half method refers to splitting a body of supposedly homogeneous data into two halves and calculating the results separately for each to assess their reliability by using Spearman-Brown formula and Guttmann split-half formula (27). Reaching a value of .70 and above represents a reliable measurement for the scale (26). In our study, Spearman Brown split-half correlation was found 0,702 and Guttman Split-half coefficient was calculated as .70 (Table 3).…”
Section: Reliabilitymentioning
confidence: 55%
“…Higher item correlation means the items exemplify similar behaviours and high level of internal consistency as well. Literature suggests on this issue that item total score correlation's being .30 and above represents that items distinguish the participants well (24,25); .20-.30 can remain in the test if necessary; .20 and less means that those items should be removed (26). At present study, even though item total score correlation of the 6th item was .27, it was decided to remain in the test since its factor load was .57 (Table 2).…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation